Antiviral and Virucidal Activities of Uncaria tomentosa (Cat’s Claw) against the Chikungunya Virus - Raquel Curtinhas de Lima; Ligia Maria Marino Valente; Débora Familiar Macedo; Luzia Maria de-Oliveira-Pinto; Flavia Barreto dos Santos; José Luiz Mazzei; Antonio Carlos Siani; Priscila Conrado Guerra Nunes; Elzinandes Leal de Azeredo (Viruses, 2024)
Uncaria tomentosa (UT) is a medicinal plant popularly known as cat’s claw belonging to the Rubiaceae family that has been reported to display antiviral and anti-inflammatory activities. The chikungunya virus (CHIKV) outbreaks constitute a Brazilian public health concern. CHIKV infection develops an abrupt onset of fever, usually accompanied by a skin rash, besides incapacitating polyarthralgia. There is no vaccine available or treatment for CHIKV infection. The present study evaluates the hydroalcoholic extract of UT bark as a potential antiviral against CHIKV. The in vitro antiviral activity of the UT extract against the Brazilian CHIKV strain was assessed using quantitative reverse transcription polymerase chain reaction, flow cytometry, and plaque assay. Results obtained demonstrated that UT inhibits CHIKV infection in a dose-dependent manner. At the non-cytotoxic concentration of 100 µg/mL, UT exhibited antiviral activity above 90% as determined by plaque reduction assay, and it reduced the viral cytopathic effect. Similarly, a significant virucidal effect of 100 µg/mL UT was observed after 24 and 48 h post-infection. This is the first report on the antiviral activity of UT against CHIKV infection, and the data presented here suggests UT as a potential antiviral to treat CHIKV infection.